Pengelolaan Sampah sebagai Pengembangan Pariwisata Berkelanjutan di Kampung Ekowisata - Istimal, Imal; Muhyidin, Ayi (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2023)
Community service program was conducted in Kampung Kranggan where the partner in this society program was Pokdarwis Ekowisata Kranggan. The activity program aimed to solve the problem of waste in Kranggan Ecotourism, both organic and inorganic waste. The devotion also pruposed to lead the strengthening waste bank management, especially in the practice of waste bank financial management. The implementation of this activity combined the method of lectures, discussions, and the provision of financial management materials and material cultivation of BSF (Black Soldier Fly) maggot larvae. The process of handling waste in the Kranggan tourist village had begun to be well organized where different methods were done based on the type of. Inorganic waste which had no economic value was processed into the furnace, while inorganic waste which had economic value was deposited into the waste bank. last, organic waste from household and industrial waste would be decomposed by maggot as a food source for maggot larvae.